Cyber-War: The Anatomy of the global Security Threat - Richards, Julian; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Cyber-War provides a critical assessment of current debates around the likelihood and impact of cyber warfare. Approaching the subject from a socio-political angle, it argues that destructive cyber war has not yet been seen, but could be a feature of future conflict.
Keywords: Science; Science; Science, general